2016
DOI: 10.3109/13813455.2016.1140212
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of neutrophil gelatinase-associated lipocalin (NGAL) in patients with non-communicable diseases: any additional benefit?

Abstract: NGAL level is best associated with serum creatinine only in patients with CKD and NGAL measurement may not be cost effective as a routine kidney function test in NCD patients in under-resourced economies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…However, in two studies conducted by Ezenwaka et al and Avci et al, along with the elevation of NGAL, serum creatinine concentration was associated with serum NGAL levels. 17,19 This contradiction in the results of the present study with those of the abovementioned studies may be due to differences in the patient population. In the present study, some CKD patients had other problems, including cardiovascular diseases and diabetes.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in two studies conducted by Ezenwaka et al and Avci et al, along with the elevation of NGAL, serum creatinine concentration was associated with serum NGAL levels. 17,19 This contradiction in the results of the present study with those of the abovementioned studies may be due to differences in the patient population. In the present study, some CKD patients had other problems, including cardiovascular diseases and diabetes.…”
Section: Resultscontrasting
confidence: 99%
“…The results of this study are in line with those of Ezenwaka and Malyszko, which showed that the serum and urinary levels of NGAL significantly increased in CKD patients. 17,18 Therefore, NGAL may be used as a diagnostic parameter in patients with acute kidney damage. Based on the findings of the present study, there was no significant association between the serum levels of NGAL and creatinine.…”
Section: Resultsmentioning
confidence: 99%
“…NGAL had an excellent and superior area under the ROC curve as compared to urea and creatinine when their diagnostic performances were evaluated using the "Area under the Receiver Operating Curve" (AUROC). This is consistent with the similar observations previously reported in patients with diabetes and hypertension [15,20]. The current study, to our knowledge; represents the first study assessing the predictive value of other early markers of renal injury, besides urea and creatinine, in two different groups of patients with sickle cell disease.…”
Section: Discussionsupporting
confidence: 92%
“…The VOC SCD group showed higher circulating levels of urea and creatinine accompanied by reduced levels of NGAL than the steady SCD group, therefore, underpinning the significance of NGAL as a biomarker of early renal damage in sickle cell subjects since NGAL correlated positively with the duration of sickle cell disease mainly when GFR was decreased. NGAL is a known protein which regulates and binds the release of catalytic iron from insulted cells and is produced by the renals in response to acute injury [19,20]. Contrary to conventional markers, such as serum creatinine and blood urea nitrogen or serum; NGAL is not considered a marker of renal function, but a reflection of structural damage of renal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation